Prognostic role of low muscle mass and strength in palliative care patients with incurable cancer: a retrospective study. Issue 3 (17th June 2021) - Mori, Naoharu; Maeda, Keisuke; Yamanaka, Yousuke; Matsuyama, Remi; Nonogaki, Tomoyuki; Kato, Ryoko; Ishida, Yuria; Shimizu, Akio; Ueshima, Junko
Abstract: Background: Wasting of muscle mass and decreasing strength have been proven to be negative prognostic indicators for patients with cancer receiving anticancer treatment. However, little is known about their role in palliative care patients. The objective of this study was to evaluate the prognostic significance of low muscle mass and strength in predicting survival among patients in palliative care. Methods: We retrospectively examined the association between muscle mass and strength and prognosis in patients with incurable solid cancer who were supported by a palliative care team at a university hospital. Psoas muscle index (PMI) at the level of the fourth lumbar vertebra was employed as the muscle mass index. Pinch grip strength (PGS) was used as the muscle strength index. Cox proportional hazards analysis was performed to evaluate the factors independently associated with overall survival. Results: A total of 78 patients were included in this study (35 male, median age 67 years). Median survival was 87.5 (95% confidence interval 50–124) days. After adjustment for age, sex, albumin, oedema, and performance status as potential confounders, loss of PMI (hazard ratio 0.998, 95% confidence interval 0.996–0.999; P = 0.003) and PGS (hazard ratio 0.73, 95% confidence interval 0.55–0.97; P = 0.030) independently predicted the overall survival. Conclusions: Low muscle mass and strength are independent predictors of survival in patients with incurable solid cancer receiving palliative care. PMI and PGS measurements may help to better assess the prognosis of patients in palliative care.